David and Goliath in the poll booth: Group size, voting power and voter turnout - Peter Bönisch; Benny Geys; Claus Michelsen (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
This article analyses how the presence of a dominant group of voters within the electorate affects voter turnout. Theoretically, we argue that both the absolute size and the relative power of a dominant group influence voters' decision-making process. The former effect derives from increased free-riding incentives and reduced social pressure to vote within a larger dominant group, while the latter effect is driven by instrumental and expressive responses-in both the dominant and dominated groups-to electoral competition between groups. Our empirical analysis of a large cross-section of German municipalities confirms this joint importance of a dominant group's absolute and relative size for voter turnout. Such effects should thus be taken into account when redesigning electoral jurisdictions through, for instance, municipal mergers or gerrymandering.
Keywords: D70; D72; H11; H40; 330; Voter turnout; Power; Group size; Merger; Gerrymandering